Pengaruh Pajak Daerah, Hasil Pengelolaan Kekayaan Dan Lain-Lain PAD Terhadap PAD Pada BPS Provinsi Lampung Tahun 2018-2022 - Febrina Affandy; Amelia Anwar; Yulistina (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of local taxes, wealth management results, and other local original income on the local original income of Lampung Province. The method used in this study is quantitative descriptive where the data processing is carried out statistically. The data used in this study are secondary data. The number of samples is 50 using the Purposive Sampling method, a group of Non-Probability Sampling, namely sampling techniques with certain considerations, namely reports on regional tax realization, wealth management results, other regional original income, and regional original income for 2018-2022. Analysis techniques are carried out through classical assumption tests, multiple linear regression tests, and hypothesis tests. Based on the results of the analysis, it can be concluded that simultaneously local taxes, wealth management results, and other local original income have a positive and significant effect on local original income, and partially each variable has a significant positive effect on regional original income.